An investigation on effect of process parameters on surface roughness and dimensional inaccuracy using Grey based Taguchi method. (2021) - Nisar, Lubaid; Banday, Bazeela; Amatullah, Mouminah; Farooq, Munazah; Thoker, Aasif Nazir; Maqbool, Annayath; Wahid, Mohd Atif
Abstract: In milling processes, product quality is estimated from the surface finish and dimensional accuracy, which are regarded as the most significant individuating characteristics in machining. A relevant and optimal machining parametric setup is critical for machining operations for enhancing the surface quality. The main purpose of this research paper is to analyse the effect of milling process parameters on surface roughness and dimensional inaccuracy of pure copper using the carbide tool. The performance characteristics of pocket milling were optimized using Taguchi's L9 orthogonal array and grey relational analysis (GRA) technique is subsequently applied to determine an optimal combination of parameters. The ANOVA technique is used to understand the importance of machining parameters on dimensional inaccuracy and surface roughness. From the experiment, it is evidently concluded that the finest combination of the parameters for pocket milling of pure copper is X3Y1Z1, i.e. at spindle speed (X) of 3000 rpm, feed rate (Y) at 200 mm/min and depth of cut (Z) at 0.1 mm. The results depicted by ANOVA demonstrate that the feed rate i.e. 77.20% is the most notable parameter affecting the dimensional accuracy and the surface roughness of the workpiece whereas spindle speed i.e. 13.72% and depth of cut i.e. 0.38% was found to be 2nd and 3rd order factors respectively.